Canadian annual review of politics and public affairs, 1993 - Leyton-Brown, David (Canadian Annual Review of Politics and Public Affairs Ser., 1999)
The year 1993 marked the changing of the political guard at both federal and provincial levels. While the cast of characters changed, however, the agendas remained much the same. Public policy was dominated by concerns about deficit and debt. Provincial governments faced declining tax revenues, which was exacerbated by reduced federal equalization payments and transfers. On the international front 1993 was the year that Parliament approved the North American Free Trade Agreement. Peacekeeping remained an important aspect of Canada's contribution to international security, but that contribution was sullied by the Somali affair. The resulting investigation affected all levels of the Department of National Defence. Featuring essays on Parliament and politics, Ottawa and the provinces, and external affairs and defence, the Canadian Annual Review of Politics and Public Affairs provides a comprehensive account of the year's events. The Canadian Annual Review has long been praised for its excellence. Known for its accuracy, readability, and insight, it offers a synoptic appraisal of the year's crises, controversies, and developments from both federal and provincial perspectives.